(untitled) (jornal of the libyan geographical society, 1997)
After more than thirty-five years of teaching geography, in many universities in the Arab world, and after this period I found that we are stuck in the same place, if not regressed from sincere beginnings in the paths of geographical development. We have retreated under the pressure of the increasing numbers of students who are often forced to study geography under the pretext of central admission and coordination in distributing students to different departments under the umbrella of the grades obtained by the student in high school, free education, the proximity of the university to the student’s place of residence, etc. We regressed, affected by our inability as geographers to present our work to others in a realistic and practical way. This prevented geography from developing, serving society, and achieving progress, while other specialists continued to dominate. Academic officials mistakenly believe that geography is nothing more than identifying the locations of cities, river courses, and a general description of natural and human geographical features on the Earth’s surface.